The Brazilian electronic theses and dissertations digital library: providing open access for scholarly information - Sílvia Barcellos Southwick (Ciência da Informação, 2006)
This paper describes a project led by the Instituto Brasileiro de Informações em Ciência e Tecnologia (IBICT), a government institution, to build a national digital library for electronic theses and dissertations – Bibliteca Digital de Teses e Dissertações (BDTD). The project has been a collaborative effort among IBICT, universities and other research centers in Brazil. The developers adopted a system architecture based on the Open Archives Initiative (OAI) in which universities and research centers act as data providers and IBICT as a service provider. A Brazilian metadata standard for electronic theses and dissertations was developed for the digital library. A toolkit including open source package was also developed by IBICT to be distributed to potential data providers. BDTD has been integrated with the international initiative: the Networked Digital Library of Thesis and Dissertation (NDLTD). Discussions in the paper address various issues related to project design, development and management as well as the role played by IBICT. Conclusions highlight some important lessons learned to date and challenges for the future in expanding the BDTD project.